Synthesis of a 68Ga-labeled peptoid?peptide hybrid for imaging of neurotensin receptor expression in vivo - Maschauer, Simone; Einsiedel, Jürgen; Hocke, Carsten; Hübner, Harald; Kuwert, Torsten; Gmeiner, Peter; Prante, Olaf (ACS Medicinal Chemistry Letters, 2010)
The neurotensin receptor subtype 1 (NTS1) represents an attractive molecular target for imaging various tumors. Positron emission tomography (PET) gained widespread importance due to its sensitivity. We combined the design of a metabolically stable neurotensin analogue with a Ga-radiolabeling approach. The Ga-labeled peptoid?peptide hybrid [Ga]3 revealed high stability, specific tumor uptake (0.7%ID/g, 65 min p.i.), and advantageous biokinetics in vivo using HT29 tumor-bearing nude mice. Because of the ability to internalize into NTS1-expressing tumor cells, [Ga]3 proved to be highly suitable for a reliable and practical visualization of NTS1-expressing tumors in vivo by small animal PET. © 2010 American Chemical Society.